2015
DOI: 10.1371/journal.pone.0122227
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Mechanical Stress Activates TRPC5 Channels

Abstract: Mechanical forces exerted on cells impose stress on the plasma membrane. Cells sense this stress and elicit a mechanoelectric transduction cascade that initiates compensatory mechanisms. Mechanosensitive ion channels in the plasma membrane are responsible for transducing the mechanical signals to electrical signals. However, the mechanisms underlying channel activation in response to mechanical stress remain incompletely understood. Transient Receptor Potential (TRP) channels serve essential functions in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 62 publications
3
33
1
Order By: Relevance
“…As a control, we used the well-characterized mechanosensitive Piezo1 and MscL channels, which under the same experimental conditions exhibited robust stretch-activated ion currents in cell and liposome membrane patches, respectively. Overall, our results contrast with the results reported in many studies describing TRP channel activation by membrane stretching, which has been reported numerous times to activate TRP channels: TRPV4 (Loukin et al, 2010), TRPA1 (Kwan et al, 2006), PKD1/ PKD2 (TRPP2) (Nauli et al, 2003), TRPC1 (Maroto et al, 2005), TRPM4 (Morita et al, 2007), TRPC5 (Shen et al, 2015) and TRPC6 (Spassova et al, 2006;Wilson and Dryer, 2014;Anderson et al, 2013;Yamaguchi et al, 2017;Dyachenko et al, 2009). Notably, inherent mechanosensitivitywhich would suggest TRP channels to be primary mechanosensorswas never provided for any of these channels.…”
Section: Discussioncontrasting
confidence: 99%
“…As a control, we used the well-characterized mechanosensitive Piezo1 and MscL channels, which under the same experimental conditions exhibited robust stretch-activated ion currents in cell and liposome membrane patches, respectively. Overall, our results contrast with the results reported in many studies describing TRP channel activation by membrane stretching, which has been reported numerous times to activate TRP channels: TRPV4 (Loukin et al, 2010), TRPA1 (Kwan et al, 2006), PKD1/ PKD2 (TRPP2) (Nauli et al, 2003), TRPC1 (Maroto et al, 2005), TRPM4 (Morita et al, 2007), TRPC5 (Shen et al, 2015) and TRPC6 (Spassova et al, 2006;Wilson and Dryer, 2014;Anderson et al, 2013;Yamaguchi et al, 2017;Dyachenko et al, 2009). Notably, inherent mechanosensitivitywhich would suggest TRP channels to be primary mechanosensorswas never provided for any of these channels.…”
Section: Discussioncontrasting
confidence: 99%
“…Additional membrane tension, in our case induced by the high-gradient magnetic field, can increase the probability of mechanosensitive channel opening44. Thus, plasma membrane mechanical stress activates transient receptor potential (TRP) channels45. Below, we calculate the mechanical forces and stress in a cell placed in an HGMF.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2+ released from intracellular stores following the opening of inositol-triphosphate receptors or Ca 2+ influx through Ca 2+ -permeable ion channels located in the plasma membrane increase global or localized intracellular endothelial [Ca 2+ ] to stimulate Ca 2+ -dependent signaling pathways. Endothelial cells are non-excitable cells (i.e., lacking voltage-gated ion channels) and the activation of Ca 2+ -permeable channels occurs by chemical and physical stimuli, such as membrane stretch caused by intraluminal pressure and shear stress 4-6 , or by soluble substances produced by autocrine or paracrine mechanisms. This review is focused on the control of endothelial cell Ca 2+ influx by reduction-oxidation reactions (redox) regulation, defined here as reactions in which the oxidation states of atoms are changed.…”
Section: Introductionmentioning
confidence: 99%